A WORKSHOP IN TEACHING ELEMENTARY SCIENCE: AN IN-SERVICE TRAINING PROGRAM FOR TEACHERS. - Brown, Clyde M. (Science Education, 1958)
The article discusses the development of a workshop in teaching elementary science. The creation of an in-service training program for teachers is a means to help elementary school teachers to teach science programs effectively. Experience is necessary to present and interpret the science principles and generalizations to the elementary students. The activities and experiences from an Elementary Science Workshop enable teachers to gain confidence in their ability to handle science and science materials and to try out the ideas with the understanding that they can learn with their students.